Profit from the source : transforming your business by putting suppliers at the core - Schuh, Christian; Schnellbacher, Wolfgang; Triplat, Alenka; Weise, Daniel (Writer on industrial procurement) (Ascent Audio, 2022)
Procurement can be your company's surprising secret weapon for winning in turbulent times. In most companies, procurement is an unglamorous, unloved part of the business. Sourcing and supplier management are strictly about costs, the thinking goes, and all that matters is playing hardball to get these as low as possible. No connection to innovation or strategy or creating positive value. Not so fast. As BCG thought leaders explain in Profit from the Source, procurement should be regarded in a new light because it has the potential to be a CEO's secret weapon in these fast-moving, disruptive times. With vivid stories and in-depth case studies, they illustrate that no other business function offers the same holistic view of a company-from suppliers who provide the organization with raw materials and components through to consumers who buy the finished product. While it's true that a core task of procurement is to control costs, the authors show how it can help businesses generate phenomenal value in innovation, quality, sustainability, speed, and risk reduction. Drawing on BCG research and the authors' first-hand experience working with some of the world's leading companies, Profit from the Source provides proven strategies to drive new bottom-line, and top-line, growth for your company.